John S. Latsis Public Benefit Foundation Research Award - Keivanidis, Panagiotis E. (My University, 2026)
Participant in a John S. Latsis Public Benefit Foundation Research Award, for the proposal 'Development of Next Generation Oxygen-barrier Materials for Organic Electronic and Dye-sensitized Solar Cell Applications', in collaboration with Assoc. Prof. Dr G. Vougioukalakis, University of Athens (GR), Greece and Dr P. Falaras, National Centre of Scientific Research "Demokritos" (GR).
Keywords: Natural sciences